2009
DOI: 10.1016/j.devcel.2009.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Dynamin Participates in the Maintenance of Anterior Polarity in the Caenorhabditis elegans Embryo

Abstract: Cell polarity is crucial for the generation of cell diversity. Recent evidence suggests that the actin cytoskeleton plays a key role in establishment of embryonic polarity, yet the mechanisms that maintain polarity cues in particular membrane domains during development remain unclear. Dynamin, a large GTPase, functions in both endocytosis and actin dynamics. Here, the C. elegans dynamin ortholog, DYN-1, maintains anterior polarity cues. DYN-1-GFP foci are enriched in the anterior cortex in a manner dependent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 71 publications
4
60
1
Order By: Relevance
“…First, our FRAP analysis indicates that GPB-1 is internalized at comparable rates across the cell cycle (Fig. 3D), whereas the rate of endocytosis varies across the cell cycle in the early embryo (Nakayama et al, 2009). Second, we found that levels of GPB-1 at the cell membrane do not increase upon 2779 RESEARCH ARTICLE Gb trafficking in C. elegans embryos Table S2 in the supplementary material for actual values and statistical analysis.…”
Section: Gb Trafficking In Early C Elegans Embryosmentioning
confidence: 74%
See 3 more Smart Citations
“…First, our FRAP analysis indicates that GPB-1 is internalized at comparable rates across the cell cycle (Fig. 3D), whereas the rate of endocytosis varies across the cell cycle in the early embryo (Nakayama et al, 2009). Second, we found that levels of GPB-1 at the cell membrane do not increase upon 2779 RESEARCH ARTICLE Gb trafficking in C. elegans embryos Table S2 in the supplementary material for actual values and statistical analysis.…”
Section: Gb Trafficking In Early C Elegans Embryosmentioning
confidence: 74%
“…Therefore, we reasoned that short exposures of dyn-1(ky51) embryos to the restrictive temperature followed by immunofluorescence analysis should provide a snapshot of the extent of GPB-1 trafficking at each stage of the cell cycle (see Materials and methods). In addition, we reasoned that such shortterm inactivation of dynamin function should not alter A-P polarity, which is also dynamin dependent (Nakayama et al, 2009), thus simplifying the interpretation of these experiments. As shown in Fig.…”
Section: Gpb-1 Endosomal Association Is Maximal During Mitosismentioning
confidence: 99%
See 2 more Smart Citations
“…LGL-1 homologs have also been shown to regulate polarized vesicle trafficking (Brennwald and Rossi, 2007), and a recent report revealed a requirement for dynamin-mediated endocytosis in maintaining polarity in the zygote (Nakayama et al, 2009). However, dynamin is enriched in the anterior of the embryo, where increased levels of endocytosis are observed, and is therefore unlikely to function directly with LGL-1 to maintain polarity.…”
Section: Reciprocal Inhibitory Interactions Between Par Proteinsmentioning
confidence: 99%